2009
DOI: 10.1186/1471-2164-10-484
|View full text |Cite
|
Sign up to set email alerts
|

Are algal genes in nonphotosynthetic protists evidence of historical plastid endosymbioses?

Abstract: Background: How photosynthetic organelles, or plastids, were acquired by diverse eukaryotes is among the most hotly debated topics in broad scale eukaryotic evolution. The history of plastid endosymbioses commonly is interpreted under the "chromalveolate" hypothesis, which requires numerous plastid losses from certain heterotrophic groups that now are entirely aplastidic. In this context, discoveries of putatively algal genes in plastid-lacking protists have been cited as evidence of gene transfer from a photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 46 publications
5
65
0
Order By: Relevance
“…An ancient green algal endosymbiont may also explain the presence of numerous "green" genes in oomycetes (nonphotosynthetic chromalveolates) and apicomplexan parasites (chromalveolates containing nonphotosynthetic plastids of red-algal origin) (Huang et al, 2004;Tyler et al, 2006;Janouškovec et al, 2010). Similarly, the presence of genes related to green algal sequences in trypanosomatid parasites (kinetoplastids) has been explained by EGT of an ancient green algal endosymbiont (Hannaert et al, 2003), but these data are open to interpretation and scenarios of ancient cryptic secondary endosymbioses in the chromalveolates and other eukaryotes have been questioned (Dagan & Martin, 2009b;Elias & Archibald, 2009;Stiller et al, 2009;Sun et al, 2010). In Monosiga, a member of the Choanozoa, which forms the sister group of the Metazoa, numerous genes of putative algal origin are present, including several genes with green algal affinities (Nedelcu et al, 2008;Sun et al, 2010).…”
Section: Spread Of Green Genes In Other Eukaryotesmentioning
confidence: 99%
“…An ancient green algal endosymbiont may also explain the presence of numerous "green" genes in oomycetes (nonphotosynthetic chromalveolates) and apicomplexan parasites (chromalveolates containing nonphotosynthetic plastids of red-algal origin) (Huang et al, 2004;Tyler et al, 2006;Janouškovec et al, 2010). Similarly, the presence of genes related to green algal sequences in trypanosomatid parasites (kinetoplastids) has been explained by EGT of an ancient green algal endosymbiont (Hannaert et al, 2003), but these data are open to interpretation and scenarios of ancient cryptic secondary endosymbioses in the chromalveolates and other eukaryotes have been questioned (Dagan & Martin, 2009b;Elias & Archibald, 2009;Stiller et al, 2009;Sun et al, 2010). In Monosiga, a member of the Choanozoa, which forms the sister group of the Metazoa, numerous genes of putative algal origin are present, including several genes with green algal affinities (Nedelcu et al, 2008;Sun et al, 2010).…”
Section: Spread Of Green Genes In Other Eukaryotesmentioning
confidence: 99%
“…The chlorophyll c-containing algae, which include brown algae, evolved soon after through secondary endosymbiosis with a red alga (95). Two scenarios are suggested for their endosymbiotic history: (a) a single endosymbiotic event followed by loss of the rhodobionts in Rhizaria, and subsequent gain of chlorobionts in the Chlorarchniophyta [the chromalveolate hypothesis (19,54)], and (b) the increasingly more favored scenario in which multiple secondary endosymbiotic events occurred (9,82,126) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Diatom and oomycete genes having affinity with red alga have limited overlap, so some researchers suggested that separate endosymbiotic events occurred before and after they diverged from their common ancestor (5,57,62,80). Support for endosymbiosis in the diatom lineage appears solid, but its occurrence prior to their divergence from oomycetes was challenged by a study that argued that other evolutionary events provide better explanations for the presence of red alga-like genes in oomycetes (80).…”
mentioning
confidence: 99%